Reception of Biblical Texts in the Unpublished Writings of Mykhaylo Maksymovych from the Holdings of the Institute of Manuscripts of the V. I. Vernadsky National Library of Ukraine - Yeremieiev, Pavlo (The Journal of V. N. Karazin Kharkiv National University. Series History, 2024)
The article considers the presence and role of biblical images in the unpublished writings of Mykhaylo Maksymovych (1804–1873), a prominent Ukrainian intellectual and the first rector of Kyiv University, with a focus on the connection between Maksymovych’s perception of the Bible and his socio-political and philosophical views. The study draws on the methodological approaches of the Cambridge school of intellectual history, theory of metaphors, and Georg Elwert’s concept of ‘we-groups.’ Based on the analysis of the scholar’s papers preserved at the Institute of Manuscripts of the V. I. Vernadsky National Library of Ukraine, the study shows that Maksymovych linked the evangelical image of the Word as the second hypostasis of the Holy Trinity with the specifics of man’s written expression, while simultaneously drawing a parallel between the image of the ‘word’ (slovo) and the term ‘Slavs.’ Maksymovych perceived the imagery of the Great Flood and the Tower of Babel as factual episodes in the history of the human race. As a follower of Friedrich Schelling, he tried to harmonize his own studies in the fields of natural history, history, and philology with biblical historiosophy. The article shows the influence of Romanticism on the reception of biblical images in the writings of Maksymovych. Based on Apostle Paul’s antithesis between the Spirit and the Letter, Maksymovych symbolically connects the image of the Spirit with ‘Holy Rus’’, and the image of the Letter with the West. In his considerations on the history of Slavic translations of the Bible, Maksymovych was influenced by the contemporary discussion on the need to translate the Holy Scriptures into modern languages, as well as by the philosophical and socio-political developments of the first half and middle of the 19th century. The article finds similarities in the views of Maksymovych and Orest Novitsky on the history of Slavic translations of the Bible and shows how characterizations of the Bible found in Maksymovych’s lecture notes from the mid-1830s were later reflected in his published works.